Novel strategy to control the elevated drizzle scale in chemical EOR pilot with unfavorable harsh environment of sandstone reservoir - Mohammad Yunus Khan (Journal of Petroleum Exploration and Production Technology)
Abstract The subject sandstone reservoir is highly heterogeneous due to amalgamated tidal-influenced distributary channels. In addition, it has an unfavorable harsh environment for chemical enhanced-oil-recovery (EOR), such as high salinity (280,000 ppm), temperature (200 °F), and divalent ions (19,000 ppm) as Ca +  + and Mg +  + . After a robust lab alkaline-surfactant-polymer (ASP) formulation design and successful field trial of the single-well-chemical-tracer-test (SWCTT), an inverted 5-spot injection pattern ASP EOR pilot was designed and field execution started. This pilot is having a challenge controlling the elevated drizzle inorganic carbonate scale at the producers. This paper elaborates on novel practical strategies to control elevated scaling risks and the re-optimization of ASP formulation adjusted to temperature variations due to the extended softened-water pre-flush phase. An extended soften-water pre-flush phase (over-flush) was considered as 7-pore-volume injection (PVI) to avoid the anticipated drizzle scaling risk. However, this over-flush strategy results in longer pilot duration, significantly higher soften water injection costs, reservoir cooling in the pilot region, and persistently high carbonate scaling in the producers. In view of this, various novel pre-flush operating strategies are investigated using high-resolution numerical simulations. The optimized pre-flush strategy was chosen based on minimal divalent ion production to control scale. Thermal simulation shows that this optimized pre-flush strategy resulted in significant cooling of the reservoir in the pilot area prior to ASP injection. Due to this cooling, the lab testing raises serious concerns about the effectiveness of the originally designed ASP formulation at reservoir temperature. As a result, the ASP formulation underwent meticulous re-tuning to ensure its robustness against temperature fluctuations and the harsh unfavorable reservoir environment. The re-optimized robust ASP formulation shows effectiveness in large temperature variations and the harsh environment of the pilot. The results of the optimized novel pre-flush strategy demonstrate that elevated drizzle scale can be controlled under harsh environments using viscous polymer slug injection (∼0.6 to 0.75 PVI) with soften water injection (~ 2 PVI). This novel strategy not only controls the scaling risk but also provides better oil desaturation, a better oil chemical ratio, less cooling effect, and a shorter pilot duration (thereby better economics) as compared to the originally designed pre-flush strategy (7PVI).